Predictive Value of Fissured Tongue in Functional Dyspepsia Combined with Depression - Jizhong Song; Qiaomin Wang; Xuemei Xu; Chaolan Lv (Gastroenterology Research and Practice)
Anxiety and depression are common in functional dyspepsia (FD) patients. Although fissured tongue (FT) is often observed in FD, its clinical value in such patients is rarely reported. We analyzed clinical data of FD patients with FT with the aim of elucidating the clinical value of FT in FD. This study suggests FD patients with different types of FT with the course of disease and the 9-item Patient Health Questionnaire (PHQ9) showed a significant difference. The PHQ9, course of disease, and self-rated dyspepsia symptoms (SRDS) correlated positively with the types of FT by the Spearman rank analysis. Epigastric pain, bloating, nausea, and SRDS showed a significant difference between FT-FD and nonfissured tongue- (NFT-) FD as well as between FD patients with and without symptoms of depression. Many FD patients also have FT, which may be associated with depressive symptoms. The longer the course of disease, the more serious the fissured tongue; thus, it may provide a predictive value for the diagnosis of depressive symptoms in FD patients.